Pemberdayaan Keluarga Tentang Pelaksanaan Senam Hamil Dalam Rangka Persiapan Persalinan - Ika Yuni Susanti; Farida yuliani (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Prenatal exercise is one of the activities in health services during pregnancy. The Indonesian Ministry of Health requires Minimum Service Standards containing 14 Steps Towards Integrated and Comprehensive Maternal Protection. Therefore, during ANC (Antenatal Care), Antenatal Education is provided, including prenatal exercise as part of the education for mothers as a form of "Love for Mothers" and part of the 14 steps towards integrated and comprehensive maternal protection. Family empowerment can be achieved by providing health education on prenatal exercise as an effort to prepare for childbirth, implemented as a community service activity. The activity was conducted by lecturers from the Midwifery Professional Study Program at Majapahit Health College in Gayaman Village, Mojoanyar District, Mojokerto Regency. The activity used lectures, simulations, and practical methods, including exercise for pregnant women. The activity was held from September to November 2025. The results of this community service activity were attended by 12 participants, pregnant women in their third trimester, with gestational ages of 28-40 weeks. The activity resulted in a significant 67% increase in knowledge and skills among pregnant women who received health education on prenatal exercise. Participants reported understanding the material and were able to repeat the exercise movements demonstrated by health workers. This activity is expected to increase family knowledge about prenatal exercise as a preparation for childbirth for mothers, thereby facilitating a smooth delivery and preventing complications and emergencies during labor